PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL DRILLINGTERHADAP HASIL BELAJAR MATEMATIKA SISWAKELAS X SMA NUSANTARA KOTA JAMBI - Rasdi . (Jurnal Ilmiah Dikdaya, 2017)
Abstract :The study was based by low mathematics learning outcomes. This is caused by teachers who are more active in the learning process, whereas students only receive materials, frequently asked questions and noted that learning math is very boring for students. Cooperative learning model snowball drilling is one of the learning models are applied in order to give a good impact on the outcome of students' mathematics learning. The population in this study were all students of class X SMA archipelago Jambi .. Sampling using probability sampling while the sample is drawn is the class Xb and Xa, in which two classes of samples are given different treatment. From the results of research conducted an average score for the class of experiment was 67.82 with a standard deviation of 10.91 and a control class averages 62.62 with a standard deviation of 11.39. As well as from the results of hypothesis test obtained t calculate equal to 1,734 and t table of 1.684. From the calculation it is seen that t is greater t table then H1 accepted or it can be concluded that the mathematics learning outcomes of students who apply cooperative learning model Snowball Drilling better than the results of learning mathematics applying conventional teaching students in class X SMA Nusantara city of Jambi. Keywords :Learning Outcomes Mathematics , Cooperative Learning Model Drilling Snowball and Conventional Teaching